2019
DOI: 10.1080/00325899.2019.1603621
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of properties of parts during MIM and sintering of recycled oxide particles

Abstract: Metal injection moulding (MIM) is an established process for high volume production of complex shaped metallic parts using commercially available feedstocks. The characteristics of parts after moulding, debinding, and sintering cannot be simply predictable from raw materials because the properties get altered with the process parameters and the corresponding levels of porosity during processing steps. In this study, physical properties, microstructure, and mechanical properties of the MIM parts have been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They confirmed that feedstock formulated with only recycled powder manifests low flowability due to high inter-particle friction inherent to the powder shape, while the addition of graphite flakes decreases the viscosity and improves the moldability of such low-cost feedstocks. A few years later, the same research group confirmed that recycled iron oxide powders can potentially be used in the production of low-cost MIM components despite lower achievable solid loadings and sintered densities when compared with virgin powders [28].…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that feedstock formulated with only recycled powder manifests low flowability due to high inter-particle friction inherent to the powder shape, while the addition of graphite flakes decreases the viscosity and improves the moldability of such low-cost feedstocks. A few years later, the same research group confirmed that recycled iron oxide powders can potentially be used in the production of low-cost MIM components despite lower achievable solid loadings and sintered densities when compared with virgin powders [28].…”
Section: Introductionmentioning
confidence: 99%